A red‐emitting indolium fluorescence probe for membranes ‐ flavonoids interactions. (6th February 2018) - Gao, Qingyun; Liu, Han; Ding, Qiongjie; Du, Jinya; Liu, Chunlin; Yang, Wei; Shen, Ping; Yang, Changying
Abstract: The red‐emitting indolium derivative compound ( E )‐2‐(4‐(diphenylamino)styryl)‐1, 3, 3‐trimethyl‐3H‐indol‐1‐ium iodide (H3) was demonstrated as a sensitive membrane fluorescence probe. The probe located at the interface of liposomes when mixed showed much fluorescence enhancement by inhibiting the twisted intramolecular charge transfer state. After ultrasonic treatment, it penetrated into lipid bilayers with the emissions leveling off and a rather large encapsulation efficiency (71.4%) in liposomes. The ζ ‐potential and particle size measurement confirmed that the charged indolium group was embedded deeply into lipid bilayers. The probe was then used to monitor the affinities of antioxidant flavonoids for membranes. It was verified that quercetin easily interacted with liposomes and dissociated the probe from the internal lipid within 60 s under the condition of simply mixing. The assessment of binding affinities of six flavonoids and the coincident results with their antioxidation activities indicated that it was a promising membrane probe for the study of drug bio‐affinities.